2020
DOI: 10.1063/5.0029068
|View full text |Cite
|
Sign up to set email alerts
|

A note on a swirling squirmer in a shear-thinning fluid

Abstract: Micro-organisms and artificial microswimmers often move in biological fluids displaying complex rheological behaviors, including viscoelasticity and shear-thinning viscosity. A comprehensive understanding of the effectiveness of different swimming gaits in various types of complex fluids remains elusive. The squirmer model has been commonly used to represent different types of swimmers and probe the effects of different types of complex rheology on locomotion. While many studies focused only on squirmers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…2020; Nganguia et al. 2020; Housiadas 2021; Housiadas, Binagia & Shaqfeh 2021), among others (Pedley 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…2020; Nganguia et al. 2020; Housiadas 2021; Housiadas, Binagia & Shaqfeh 2021), among others (Pedley 2016).…”
Section: Introductionunclassified
“…Chlamydomonas) part of their body. The squirmer model has therefore become a widely used generic locomotion model for various problems in low-Reynolds-number swimming, including nutrient uptake by microorganisms (Magar, Goto & Pedley 2003;Magar & Pedley 2005;Michelin & Lauga 2011;Eastham & Shoele 2020), optimization (Michelin & Lauga 2010), hydrodynamic interactions (Ishikawa, Simmonds & Pedley 2006;Drescher et al 2009), collective motion Ishikawa, Simmonds & Pedley 2007), inertial effects (Wang & Ardekani 2012;Chisholm et al 2016) and swirling motion (Pedley, Brumley & Goldstein 2016;Binagia et al 2020;Nganguia et al 2020;Housiadas 2021;Housiadas, Binagia & Shaqfeh 2021), among others (Pedley 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Toward this goal, we close this article with several suggestions for future research directions: Effect of ECM mechanics and rheology on propulsion efficiency : The motion efficiency (and thus therapeutic efficacy) of SPPs has been shown recently to depend on the topology, rheological properties, and viscoelastic properties of the medium. Recently, it was reported that shear-thinning effects cause a substantial enhancement in the propulsion of helical microswimmers [ 114 ]. On the other hand, it is also known that as ECM becomes stiffer and denser, the velocity is attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that ECM viscoelasticity influences fundamental cell processes such as differentiation, spreading, migration, and ECM synthesis, and plays a key role in the procession of diseases such as fibrosis and cancer [ 49 ]. Considering the growing body of literature on microscale self-propulsion in shear-thinning [ 113 , 114 , 115 ] and viscoelastic media [ 116 , 117 ], it is reasonable to expect that ECM viscoelasticity will influence the efficiency of the self-propulsion. Accordingly, to develop SPPs that are attractive for biomedical applications in drug delivery in human tissues, it is critical that the swimming performance of SPPs be tested in environments that possess similar viscoelastic characteristics to in vivo human tissues.…”
Section: Self-propelled Particles Movement In Ecmmentioning
confidence: 99%
“…Microswimmers encounter diverse fluidic environment during their course of motion [42][43][44][45][46][47][48][49] . The comprehensive studies on the effect of fluid reveal that the rheology of the surrounding medium can strongly affect the motility of microsswimmers 5,23,50,51 An increase in translational velocity but a decrease in the rotational diffusion in viscoelastic fluids compared to Newtonian fluids for the E.coli has been established 52 .…”
Section: Introductionmentioning
confidence: 99%